"The Deliverer Will Come": Investigating Paul's Adaptation of Divine Conflict Traditions in Romans. (October 2022) - Ryan, Scott C.
In recent years, scholars have shown renewed interest about the ways in which Paul's letters utilize divine conflict traditions. In Romans 5–8 and 16:20a Paul frames the human predicament in terms of cosmic conflict and adapts divine conflict traditions, but other passages also reflect the apostle's adaptations of these motifs. This essay will first consider the broad contours of portrayals of God as warrior in Israel's Scriptures. Discussion will then focus on vocabulary and themes in Rom 1:18–32 and 11:25–32 to demonstrate that in these texts Paul also works with images related to divine conflict. Considering these passages from Romans alongside the divine conflict traditions of earlier voices–especially the Israelite prophets–assists in understanding Paul's comments on wrath and judgment and assists in understanding Paul's comments on wrath, judgment, and deliverance.